2014
DOI: 10.1039/c4py00349g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, semi-automated convergent synthesis of low generation triazine dendrimers using microwave assisted reactions

Abstract: Microwave assisted synthesis allows for the rapid access of low generation triazine dendrimers in high yields. Products include a macromonomer and alkyne functionalized dendrimers from generation one to three. Using a microwave assisted, convergent synthetic approach, two nucleophilic aromatic substitution reactions are executed on cyanuric chloride in 10 min at 60 C using primary amines. Substitution of the resulting monochlorotriazine with a diamine requires 95 C for 30 min. Purifications are accomplished us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…We have shown that microwave irradiation substantially decrease times of reaction in low generation dendrimers synthesized by convergent route. 10 In light of this success and motivated by the long standing interest of performing an easy and fast synthesis, we decide to extend this chemistry to large generation triazine dendrimers using a divergent approach. We have shown that triazine dendrimers may have potential applications in many areas based on the ability to create versatile structures including areas in gene and drug delivery as well as materials science.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that microwave irradiation substantially decrease times of reaction in low generation dendrimers synthesized by convergent route. 10 In light of this success and motivated by the long standing interest of performing an easy and fast synthesis, we decide to extend this chemistry to large generation triazine dendrimers using a divergent approach. We have shown that triazine dendrimers may have potential applications in many areas based on the ability to create versatile structures including areas in gene and drug delivery as well as materials science.…”
Section: Introductionmentioning
confidence: 99%
“…Particles from the same batches as those described by us in the earlier studies [22][23][24][25][26] were used in this study. Synthesis and characterization of triazine dendrimers were also described earlier [27][28][29] . The complete list of reagents and their sources is available in the supplementary materials.…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…A fast, simple and single‐stage microwave synthesis of water‐soluble PAMAM dendrimers with the same polymeric Jeffamine ® T‐403 core and two monomeric, en and diethylenetriamine, cores was developed . In addition, microwave synthesis allows to obtain triazine dendrimers of lower generations (one to three) and odd generations to G9 with high yields …”
Section: Preparation Of Chelating Dendrimersmentioning
confidence: 99%